Francisco's kites - Klepeis, Alicia, 1971- (Pinata Books/Arte Público Press, 2015)
Francisco misses his village in El Salvador, and especially flying a kite with his friends, but Mamá can't afford to buy a kite, so he gathers discarded materials around his apartment building and makes his own, which catches the eye of a store owner and leads to a wonderful project.